1973
DOI: 10.1073/pnas.70.5.1526
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Reticulocyte Membrane Proteins by Membrane-Free Polyribosomes

Abstract: Intact rabbit reticulocyte cells synthesize two predominant species of membrane polypeptides; at least 10 reticulocyte membrane polypeptide species are not produced by the cells. Cell-free extracts of reticulocytes, free of any membranes or membrane-bound polyribosomes, synthesize large amounts of these two membrane polypeptides; one of these polypeptides appears to be modified, probably by loss of 20-40 amino acids, after it is incorporated into the membrane. Deprivation of hemin results in inhibition of synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…Subunits of several mitochondrial enzymes are believed to be synthesized on cytoplasmic ribosomes and to be subsequently transferred to their locations in the mitochondria (22). Cytoplasmic pools of polypeptides play an important role in the biosynthesis of plasma membranes, as has been demonstrated previously for reticulocytes (23), and in the assembly of the viral envelope (24).…”
Section: Discussionmentioning
confidence: 99%
“…Subunits of several mitochondrial enzymes are believed to be synthesized on cytoplasmic ribosomes and to be subsequently transferred to their locations in the mitochondria (22). Cytoplasmic pools of polypeptides play an important role in the biosynthesis of plasma membranes, as has been demonstrated previously for reticulocytes (23), and in the assembly of the viral envelope (24).…”
Section: Discussionmentioning
confidence: 99%
“…Biosynthetic studies with rabbit reticulocytes have shown that two nonglobin proteins of 33,000 and 56,000 daltons (8) are made by the free polyribosomes in the cytoplasm and then attach to the inner surface of the membrane (9). The latter protein loses about 30 amino acids with incorporation into the membrane.…”
mentioning
confidence: 99%
“…8) Furthermore, the hemin effect is not specific to the synthesis of globin. Recently, it has been shown that hemin is necessary for maximal protein synthesis of the nonglobin proteins of the reticulocyte (27,(37)(38)(39), as well as for Krebs II ascites tumor cells (40), platelets (41), and brain and liver cells (34). Thus, one may speculate that the suppression of heme synthesis and enhancement of HCR possibly might have many more complex effects rather than solely the inhibition of hemoglobin synthesis and production of hypochromic red cells.…”
Section: Discussionmentioning
confidence: 99%